242 Sufficient sleep attenuates the impact of COVID-19 pandemic on executive function decline in late adolescents and young adults. (3rd May 2021) - Ji, Xiaopeng; Saylor, Jennifer
Abstract: Introduction: Executive function (EF), which shows continued development into early adulthood, is essential to build resilience to cope with COVID-19-related social and environmental changes. However, how sleep interacts with the pandemic on affecting EF remains unclear, particularly among late adolescents and young adults. This study examined (1) the impact of COVID-19 pandemic on sleep and EF and (2) whether sleep moderated pandemic-related changes in EF among young people aged 18-21 years old. Methods: Between April and May 2020, university students with baseline data on sleep and EF (Spring and Fall semesters in 2019) available were invited to this follow-up study. Sleep duration, mid-sleep times, social jetlag (the difference between mid-sleep times on weekdays and weekends) and sleep latency were assessed using 7-day sleep diaries. Participants also completed the Pittsburgh Sleep Quality Index (PSQI), the Morningness/Eveningness Questionnaire, and the Behavior Rating Inventory of Executive function which yielded Global Executive Composite (GEC) scores. Paired t-test and multilevel random-effects models (STATA 16.0) estimated the associations. Covariates in multilevel models included age, sex, race, family income, parental education, COVID status, and health behaviors. Results: Forty participants (19.25±1.12 years old) had paired data before and during COVID-19 pandemic. Participants slept 24 min longer (t= -2.07, p=0.03) but had increased sleep latency (t=-1.83, p=0.07) during the pandemic compared to pre-COVID baseline. Mid-sleep times shifted 40 min later (t= -3.22, p=0.003) during the pandemic. In multilevel models, GEC scores increased during pandemic (b=3.15, p=0.03) versus baseline, suggesting decreased executive function. Sleep duration (β=-4.72, p=0.03) significantly interacted with assessment time (before/during COVID-19), with increasing sleep duration attenuating the decline in EF during pandemic versus baseline. Although there was no interaction with COVID-19 pandemic, poor sleep quality (PSQI>5) was independently associated with decreased EF (B=4.69, p=0.02). Other sleep variables were not associated with EF nor moderators. Conclusion: Compared with pre-COVID-19 baseline, young people report longer sleep duration, later sleep phase, increased sleep latency, and worse executive function during the pandemic. Sufficient sleep represents a resilience factor against executive function decline during this unprecedented crisis. Support (if any): No